Evaluation of Long-Term Wastewater Treatment Performances in Multi-Soil-Layering Systems in Small Rural Communities - Kuniaki Sato; Toshiyuki Wakatsuki; Noriko Iwashima; Tsugiyuki Masunaga (Applied and Environmental Soil Science)
Multi-soil-layering (MSL) wastewater treatment systems consist of soil units (soil mixture blocks, SMB) arranged in a brick-like pattern surrounded by permeable layers of zeolite or alternating particles of homogeneous sizes that allow for a high hydraulic loading rate. This study evaluated the performances of MSL systems that have been operating for 17 to 20 years in small rural communities. Even though 20 years had passed since this system was installed, high organic matter treatment performance continued. Nitrogen removal was higher than with conventional soil systems. Two of the MSL systems continued to show high phosphorus removal performances, whereas in the third system, the adsorbing capacity was relatively low, requiring further investigation. Treatment performances were largely dependent upon the structure of the MSL systems. It appeared that improving the structure to enhance the contact efficiency between the wastewater and the soil in SMB was important for enhancing treatment performances. The combined use of existing wastewater treatment systems with the MSL system was effective for preventing environmental pollution over a long period.